2022
DOI: 10.1093/jamia/ocac022
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and strategies for promoting health equity in virtual care: findings and policy directions from a scoping review of reviews

Abstract: Objective We sought to understand and synthesize review-level evidence on the challenges associated with accessibility of virtual care among underserved population groups and to identify strategies that can improve access to, uptake of, and engagement with virtual care for these populations. Materials and Methods A scoping review of reviews was conducted (protocol available at doi: 10.2196/22847). A total of 14 028 records we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…The use of technology required to access virtual care raises important equity concerns. Previous studies have reported lower rates of technology adoption and increased barriers to virtual care among older patients, racial and ethnic minority groups, and those of lower socioeconomic status [ 21 24 ]. In our study, patients accessing virtual urgent care services were mostly young, well educated, English-speaking females with a primary care provider, suggesting access to virtual care may exacerbate existing health inequities among patients using virtual care compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The use of technology required to access virtual care raises important equity concerns. Previous studies have reported lower rates of technology adoption and increased barriers to virtual care among older patients, racial and ethnic minority groups, and those of lower socioeconomic status [ 21 24 ]. In our study, patients accessing virtual urgent care services were mostly young, well educated, English-speaking females with a primary care provider, suggesting access to virtual care may exacerbate existing health inequities among patients using virtual care compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review of scoping reviews also illustrated the complexities of engaging individuals in web-based health services, recognizing how an individual’s culture and perceived effectiveness of telehealth technologies is intertwined not only with digital literacy but also the social and structural determinants of health [ 42 ]. It is likely that there are other factors that we did not measure, which are stronger predictors of completion of the VC delivery mode (eg, digital literacy and trust in technology).…”
Section: Discussionmentioning
confidence: 99%
“…Measuring barriers and enablers to telehealth participation as well as appropriate uses and how these vary across places and populations may help address health care inequities. These health care and broadband infrastructure metrics may help provide the information needed to improve equity through telehealth 30…”
Section: Understanding the Evidence Base For Telehealth In Us Public ...mentioning
confidence: 99%